Perspectives: THE COLONIAL MIND IN POST-SECONDARY EDUCATION - Vickers, Patricia (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 2002)
ABSTRACT. This article links my personal experience as a First Nations doctoral student to Paulo Freire’s teachings on oppression. The spirit of his writing has inspired me to work toward transformational change. I also draw on other discussions of colonialism including the writings of Edward Said. I explore, in the Canadian context, what I refer to as the "colonial mind." The colonial mind is exhibited in relationships and produces polarized behaviours that result from superior - inferior stances. Oppressive attitudes and actions are often unconscious, unintentional, and trans-generational. The First Nations student must identify oppression within academic institutions and the cultural oppression that exists in both general society and academic institutions. Both forms of oppression, institutional and cultural, exhibit similar features and grow from the same root of superior - inferior dynamics. Freedom from oppression, both cultural and institutional, requires the individual to (a) identify the beliefs that support oppressor/oppressed dynamics; (b) identify the actions and attitudes that perpetuate oppression and; (c) exert the will to change personal behaviours in relationships with others. The perspective in this manuscript does not represent a voice for all First Nations people; rather, this is a personal perspective based on my experience as both a student and a teacher. L’ESPRIT COLONIAL DANS L’ENSEIGNEMENT SUPÉRIEUR RÉSUMÉ. Cet article établit un lien entre mon expérience personnelle d’étudiante autochtone de doctorat et les enseignements de Paulo Freire sur l’oppression. L’esprit de son ouvrage m’a incitée à vouloir des changements en profondeur. Je m’inspire également d’autres analyses du colonialisme, notamment des écrits d’Edward Said. Dans le contexte canadien, j’étudie ce que j’appelle « l’esprit colonial ». L’esprit colonial se manifeste dans les rapports humains et aboutit à des comportements polarisés découlant de positions de supériorité-infériorité. Les actes d’oppression sont souvent inconscients, involontaires et se transmettent de génération en génération. L’étudiant autochtone doit cerner l’oppression au sein du milieu universitaire et l’oppression culturelle qui existe à la fois dans la société en général et dans le milieu universitaire. Les deux formes d’oppression, institutionnelle et culturelle, présentent des caractéristiques analogues et découlent de la même dynamique supériorité-infériorité. Pour se libérer de l’oppression, aussi bien culturelle qu’institutionnelle, l’individu doit a) préciser les croyances qui favorisent la dynamique oppresseur-oprimé; b) cerner les actes et les attitudes qui perpétuent l’oppression; et c) être animé du désir de modifier des comportements personnels par rapport aux autres.